Influence of alkyl chain length in S, N-heteropentacenes on the performance of organic solar cells12. (15th March 2018) - Leitner, Tanja D.; Vogt, Astrid; Popović, Duško; Mena-Osteritz, Elena; Walzer, Karsten; Pfeiffer, Martin; Bäuerle, Peter
Abstract : Acceptor-substituted S, N -heteropentacenes with systematically varied alkyl side chains were prepared and implemented as donors in vacuum-processed OSCs giving devices with efficiencies in the range of 4–6%. An odd–even effect with respect to the length of the alkyl side chains is noted. Abstract : A novel family of alkyl-substituted S, N -heteropentacenes SN54–6 with a systematic variation of the alkyl side chains from methyl to hexyl is presented. The parent heteroacene series4 and the acceptor end-capped series5 and6 were synthesized and characterized with respect to their structure–property relationships. The dicyanovinyl (DCV) end-capped derivatives6a–f were implemented as donors in vacuum-processed bulk-heterojunction solar cells with fullerene C60 as acceptor, their photovoltaic behaviour studied, and structure–device relationships discussed. The devices exhibited power conversion efficiencies (PCE) in the range of 4–6% and interestingly a correlation between the length of the alkyl side chains and the photovoltaic performance of the resulting devices was discovered: an odd–even effect with higher values for the even-numbered alkyl chains. Atomic force microscopy (AFM) studies on the active layer surfaces gave hints for the explanation of this effect.